Intestinal microsporidiosis in Strasbourg from 2014 to 2016: emergence of an Enterocytozoon bieneusi genotype of Asian origin - Greigert, Valentin; Pfaff, Alexander W.; Abou-Bacar, Ahmed; Candolfi, Ermanno; Brunet, Julie (Emerging microbes & infections, 2018)
Microsporidia cause opportunistic infections in highly immunodeficient individuals. Few studies on the epidemiology of these infections have been conducted in France. Between 2014 and 2016, we undertook a study to estimate the prevalence and circulating genotypes of this fungus-related micro-organism among the population of Strasbourg University Hospital. Samples were collected from hospitalized patients and analyzed using microscopy and molecular assays. Strains from positive subjects were sequenced for genotyping. Only 7/661 patients (1.1%) were positive for microsporidia, and the only species identified was Enterocytozoon bieneusi. Two patients presented immunodeficiency linked to AIDS, and five transplant recipients presented immunodeficiency linked to immunosuppressive therapies. Only five patients received specific antimicrosporidial treatment, but clinical outcomes were good in all cases. We identified four genotypes: A and D in patients with AIDS, and C and S9 in transplant recipients. To date, genotype S9 has been described only once. This genotype is similar to those found in farm animals in China. Because some of these animals have been introduced to Central Europe, we postulate that this genotype might be of Asian origin. Thus, genotyping microsporidial strains may be of epidemiological and clinical interest to identify potential outbreak sources depending on the infecting strains.